Trunk stability, muscular fitness and sport performance level in competitive judokas - López Valenciano, A.; Barbado, D.; Juan Recio, C.; Montero Carretero, C.; Dieën, J. H. V.; Vera Garcia, F. J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
INTRODUCTION: The development of the ability to stabilize the trunk/core may improve the performance of a judoka through improvement of body balance control and optimization of force transmission from the lower extremities to the upper limbs. However, to our knowledge, evidence on relationship between trunk stability and level of athletic performance in judo is lacking. The aim of this study was to compare trunk stability and trunk muscular fitness between national and international level judokas. METHODS: Twenty-five competitive judokas (8 international and 17 national level judokas) took part in this study. A battery of static and dynamic tests was performed to measure trunk balancing while sitting on stable and unstable seats placed on a force plate (Kistler 9286A). Postural and dynamic sway were assessed by analyzing the mean radial displacement of the centre of pressure (COP). Sudden and unexpected trunk loads in anterior, posterior and lateral directions, were applied to the thorax by a pneumatic mechanism, while the participant was seated with the pelvis fixed. Trunk angular displacement was measured and the damping and stiffness coefficients of the trunk were calculated from the first 110 ms of data after loading. An isokinetic test was used to assess trunk muscle fitness, which consisted of 4 trials of 15 maximal flexion-extension exertions at 120º/s (ROM = 50º). Absolute and relative peak torque and maximum work were calculated to assess trunk muscular strength, and the endurance ratio, maximum work ratio and final fatigue ratio were calculated to assess muscular endurance. RESULTS: International level judokas showed lower trunk angular displacement and higher damping after anterior directed loading, and higher relative and absolute peak torque and relative maximum work during maximal extension exertions, than national level judokas. DISCUSSION: Trunk response to sudden perturbations and trunk extensor strength measures were different between national and international level judokas. Trunk stability against loading may be determinant of high performance in judo, as it may help competitive judokas to keep balance during defensive and offensive techniques. In addition, trunk extensor strength, rather than trunk flexor strength, appears to be related to high performance in judo.